Exergy, economic, environmental and sustainability analyses of possible regenerative evaporative cooling device topologies - Kashyap S.; Sarkar J.; Kumar A. (My University, 2025)
Due to the increase in cooling load globally, it needs to find an efficient, environment-friendly and sustainable cooling technology. The regenerative evaporative cooler is a better option in this direction. The regenerative evaporative cooler can be possible in different configurations depending on the primary air, secondary air and water flow directions, and it is required to select a thermodynamically, economically and environmentally best sustainable configuration. Hence, this paper numerically simulates exergy, economic and environmental parameters of regenerative evaporative cooler using the generalized model. All possible configurations of the regenerative evaporative cooler are compared based on exergy destruction, exergy efficiency, specific total cost, CO2 emission and sustainability index. The effect of the geometric and operating parameters on the performance of all configurations is investigated. The analysis concluded that lower channel gap, extraction ratio and air flow rate improve exergetic efficiency and sustainability index and reduce CO2 emission. Within studied configurations of the regenerative evaporative cooler, A and H are best in terms of higher exergy efficiency, lower specific total cost and higher sustainability index. © 2020 Elsevier Ltd